A comparison between trap and flotation methods of sampling in quantifying mite exposure - Htut, T; Higenbottam, T; Vickers, L; Hyndman, S; Maunder, J; Peock, A; Gill, G; Darwin, R; Anderson, P (1998)
Background: Quantification of mite exposure by determining mite levels in dust using a flotation technique has considerable shortcomings due to non-reproducibility of vacuum sampling, and high variability in the mite extraction efficiency. Mite traps have been reported to be more efficient, simpler and more standardised than dust sampling as the mite extraction phase is not required. The trap-method was used alongside dust sampling in a study investigating the role of dehumidifiers in dust mite control. Thus a comparison of the methods was possible. Methods: Dust from the top surface of mattresses in 51 homes, 25 with dehumidifiers in the bedroom, was collected in two rounds of sampling, 12 months apart. After vacuum sampling on each occasion, two pieces of 20x 22.5 cm transparent adhesive film were placed on the mattress-top to trap mites. The dust was quantified for mite and Der p 1 levels by the flotation method and enzyme immunoassay. Mite levels obtained from the dust and traps were compared using Wilcoxson's test, and Bland and Altman's test for the agreement between the two methods. Results: Both methods correlated with the Der p 1 levels. There was agreement between the trap and flotation techniques as >95% of the differences between the two methods lay within two standard deviations. The traps gave significantly higher mite counts than the dust samples (p<0.001) when the median was >11/m 2 (range 0-4144), but no difference at very low counts. A significant reduction in the mite levels in the dehumidifier group was detected at the end of the trial only in the trap data (p<0.03), but not in the dust data (p>0.2). Conclusion: The trap method was more effective than the flotation method in sampling mites. Although both methods could be used interchangeably, traps were more sensitive in detecting small changes. The compliance and practicability of the trap method was excellent. It can be used in field studies for quantifying mite exposure.